PENGARUH PERBANDINGAN TEPUNG UBI JALAR UNGU DAN TEPUNG KEDELAI TERHADAP KARAKTERISTIK COOKIES - Utami, Putu Andi Sri; Sugitha, I Made; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This study aims to determine the effect of purple sweet potato flour and soybean flour to the characteristics of cookies produced and the ratio of purple sweet potato flour and soybean flour so that it can produce cookies with the best characteristics. The experimental design used was Completely Randomized Design with the ratio of purple sweet potato flour and soybean flour which consists of 6 levels: 100%:0%; 90%:10%; 80%:20%; 70%:30%; 60%:40%; and 50%:50%. The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with The Duncan Multiple Range Test. The research showed that 70% of purple sweet potato flour with 30% of soybean flour produced the best cookies with characteristics of water content 3.37%, ash content 1.43%, protein content 12.73%, lipid content 24.89%, carbohydrate content 57.58%, antioxidant activity 10.09%, color rather liked, rather liked and very crispy texture, taste liked, aroma liked, and overall acceptance liked.